Will is not enough: coping planning and action control as mediators in the prediction of fruit and vegetable intake - Godinho, C. A. (2014)
Objectives: This study investigates the joint role of coping planning and action control as volitional predictors of changes in the daily consumption of fruit and vegetables. Design: In a longitudinal online survey, 203 participants completed assessments at baseline (Time 1), 1 week (Time 2), and 2 weeks later (Time 3). Methods: Structural equation modelling was used to test a series of three nested models. In Model 1, only intention predicted behaviour; in Model 2, both coping planning and action control were tested as mediators between intention and behaviour; and Model 3 specified coping planning and action control as sequential mediators between intention and behaviour. Results: Model 3 provided the best fit to the data. The mediating role of coping planning and action control between intention and fruit and vegetable intake was confirmed, whereby multiple mediation occurred in a sequential manner, with coping planning preceding action control. Conclusions: For motivated individuals who are not yet following the recommendations for fruit and vegetable consumption, coping planning and action control reflect a psychological mechanism that operates in changes in fruit and vegetable consumption.